Ubodzy w diecezji augustowskiej czyli sejneńskiej - Jemielity, Witold (Prawo Kanoniczne, 2003)
Each parish had to provide maintenance to all the poor living on that area. Some of them used to live by the church in the parish houses called hospitals while others lived in villages. Few hospitals used the money put down to their bank accounts by the rich, the others were supported thanks to the alms of the parishioners and help of the parish-priest. Residents of hospitals cleaned the church, rang the bell for church, served during the mess or helped on the farm. Other poor people were called beggers. The parish-priest kept a record of beggers, issued certificates qualifying them to alms on the area of his parish, encouraged his parishioners to generosity. Civil authorities often criticized the quantity of beggers, idlers and wanderers. They tried to find any solution even by sending such people to the army or by forcing them to work. They mainly stressed that that was the duty of the parish. After the January Uprising communes got self-governed powers and since then they took care of the poor. On the turn of the century charity organizations came into being.